An Expedient Synthesis of a Functionalized Core Structure of Bielschowskysin - Nicolaou, K. C. (2011)
Photons in action: A five-step synthesis of a functionalized tricyclo[9.3.0.0]tetradecane ring system of the marine natural product bielschowskysin has been achieved through an exquisite intramolecular [2+2] photocycloaddition reaction of a macrocyclic precursor.